Law and Social Reality in Kosovo and Metohija Today - Simić, Igor S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Since the emergence of law, the establishment of a legal system and the codification of social norms have served to protect the fundamental values underpinning every society, community, and ultimately, humanity as a whole. These values have evolved over time through various forms of social interactions. Throughout this evolution, social values changed in accordance with the needs of the society, while being shaped by the specific characteristics and limitations of particular communities and territories. In the modern era, when technological and scientific development has transformed the planet Earth into a “global village,” social values are increasingly promoted beyond territorial and communal boundaries. In Europe, the creation of the European Union has fostered a political and economic system founded on respect for core social values such as freedom, human rights, tolerance, honesty, and justice, collectively promoted as European values. To protect, enhance, and preserve these values, law has been used to regulate social behaviour, not to distance people from shared norms, but to strengthen interpersonal relations and thereby ensure social balance. Consequently, these social (now promoted as European) values have become both the standard and criterion for assessing the degree of democratization within European societies. Their observance by state institutions has, in turn, become a kind of “entry ticket” for EU membership. The turbulent history of the Western Balkans has been most acutely reflected in Kosovo and Metohija. Here, law and social norms have developed through complex socio-political processes, shaped by interactions among people of different religious and ethnic backgrounds, as well as by the succession of diverse political systems. Recurrent conflicts—driven primarily by political, ethnic, and religious motives—have repeatedly undermined these vital social values. The political, economic, and demographic dominance of certain ethnic groups has often led to violations of the legal rights of smaller communities, to the point where fundamental human rights and social values were disregarded. The newly-established “normality” has thus been characterized by the erosion and persistent of legal norms designed to safeguard those values. This paper examines the interrelation between law and social values through an analysis of their practical implications in the lives of the Serbs in Kosovo and Metohija today—twenty-four years after the NATO aggression against the Federal Republic of Yugoslavia—while taking into account the historical developments that have shaped the current social and legal realities in this region.
Keywords: law; norms; social values; European values; social reality; Kosovo and Metohija